Dental implant surfaces treated with phosphoric acid can modulate cytokine production by blood MN cells - Fernando Luzía França; Adenilda Cristina Honorio-França; Mariana Silva Honorio; Fabiana Helen da Silva; Mahmi Fujimori; Eduardo Luzía França; Fernando Gabriel da Silva Araújo (Brazilian Oral Research)
Abstract: The study characterizes dental implant surfaces treated with phosphoric acid to assess the effects of acid treatment on blood cells and correlate them with cytokine levels. The implant surfaces examined were divided into untreated metal surface (US; n = 50), metal surface treated with phosphoric acid (ATS; n = 50) and cement surface (CS; n = 50) groups. The samples were characterized by scanning electron microscopy (SEM) and rheometry. The implants were incubated with human blood mononuclear cells for 24 h, with surface rinsing in the ATS treatment. Cell viability was determined by colorimetric methods and cytokines in the culture supernatant were quantified using flow cytometry. In the ATS group, the surface porosity and contact surface were increased and plaques were observed on the surface. The blood flow and viscosity curves were similar among the treatments, and the high cell viability rates indicate the biocompatibility of the materials used. An increase in the levels of IL-2, IL-4, IL-6, IL-10 and TNF-α was observed in the ATS and CS groups. There were positive correlations between IL-10 and IL-2 levels and between IL-10 and IL-4 levels in the culture supernatant of the ATS group. The results suggest that implant surface treatment with phosphoric acid activates the production of inflammatory cytokines. The increased cytokine levels can modulate the immune response, thereby improving biofunctional processes and promoting the success of dental implants.